Combustion of single particles from sewage sludge/pine sawdust and sewage sludge/bituminous coal under oxy-fuel conditions with steam addition. (1st January 2020) - Lei, Kai; Zhang, Rui; Ye, Buqing; Cao, Jin; Liu, Dong
Highlights: The combustion of single particles from SS/PS and SS/BC was studied. Increasing SS blending ratio speeds up ignition but decreases combustion temperature. The addition of steam promotes ignition and combustion. Abstract: Co-pelletization of sewage sludge (SS) and conventional fuels for combustion is considered to be a feasible SS disposal method. Oxy-fuel combustion is recognized as a promising technology to reduce the emission of CO2 . In practical applications, the combustion atmosphere in oxy-fuel boiler is O2 /CO2 /H2 O, which is different from that in the conventional boiler (O2 /N2 ). Therefore, the effects of gas composition on the combustion characteristics of boiler fuels should be both taken into consideration. In this work, the SS/pine sawdust (PS) and SS/bituminous coal (BC) blended fuel particles were prepared, and the single particle combustion experiments were conducted in O2 /N2, O2 /CO2 and O2 /CO2 /H2 O atmospheres. The influences of SS blending proportion and gas composition on combustion characteristics of fuel particles were analyzed. The results reveal that increasing the blending proportion of SS from 20 to 40 wt% decreases the ignition delay time, burnout time and combustion temperature. The substitution of N2 by CO2 increases the ignition delay time and burnout time, while decreases the combustion temperature. Replacing CO2 by 10 vol%, 20 vol% and 30 vol% H2 O decreases the ignition delay time and burnout time, while increases the combustion temperature.